2022
DOI: 10.1007/s41324-022-00481-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform effect of COVID-19 lockdown on the air quality in different local climate zones of the urban region of Kochi, India

Abstract: Deterioration of ambient air quality associated with urbanisation is a serious concern in many parts of the world. In India, air pollution, primarily due to particulate matter, has increased exponentially in the last few decades due to rapid urbanization, industrialization and population growth. This study investigates the non-uniform influence of COVID-19 lockdown on the ambient air quality of three distinct local climate zones (LCZs) within the urban region of Kochi (Kerala, India). The analysis of the air p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, the concentration of various air pollutants returned to its original level (i.e., PRLD) after relaxing the lockdown measures during the PTLD period. Thomas et al ( 2022 ) noted such behaviour of air pollutants in the Kochi urban area of Kerala. However, most of the pollutants recorded at KN show a continuation of the declining trend of the LD period in the PTLD period also.…”
Section: Resultsmentioning
confidence: 93%
“…However, the concentration of various air pollutants returned to its original level (i.e., PRLD) after relaxing the lockdown measures during the PTLD period. Thomas et al ( 2022 ) noted such behaviour of air pollutants in the Kochi urban area of Kerala. However, most of the pollutants recorded at KN show a continuation of the declining trend of the LD period in the PTLD period also.…”
Section: Resultsmentioning
confidence: 93%
“…. A study in the southwest coastal region of India found that the changes in PM 2.5 , PM 10 , NO 2 and O 3 concentrations relative to the lockdown period ranged from + 11.5% to + 38.3%, from + 1.3% to + 36.0%, from − 5.1% to + 46.1% and from − 21.2% to + 4.1%, respectively(Thomas et al, 2023). The study conducted in Campania, Italy revealed an increase in pollutant concentrations at all stations following the lifting of lockdown measures with signi cant changes observed for NO 2 concentrations ranging between + 32% to + 63%(Cardito et al, 2023).…”
mentioning
confidence: 99%